Fangchinoline Protects Against Renal Injury in Diabetic Nephropathy by Modulating the MAPK Signaling Pathway - Jiang, Yingsong; Liu, Jiguo; Zhou, Zemei; Liu, Ke; Liu, Chun (Experimental and Clinical Endocrinology & Diabetes, 2018)
In this study, we evaluated the nephroprotective effects of fangchinoline in rats with diabetic nephropathy (DN). DN was induced by feeding a high-fat diet for 4 weeks and administering a single dose of streptozotocin (STZ) (30 mg/kg) intraperitoneally. The rats were split into groups; one group received oral fangchinoline (3 mg/kg) per day for 8 weeks. After completion of the 8-week study period, biomedical and inflammatory markers were evaluated in serum and urine, and oxidative stress was estimated in kidney tissues. In addition, Western blot assays, reverse transcription-polymerase chain reaction, and immunohistochemical analyses were performed in the kidney tissues of DN rats. The results suggest that treatment with fangchinoline attenuated the biochemical marker changes induced by DN in blood and urine. Moreover, a significant (p<0.01) reduction in inflammatory markers in serum was found in the fangchinoline group compared to the controls. Immunohistochemical analyses also revealed that treatment with fangchinoline significantly reduced the expression of collagen IV and CD31 in the kidneys compared to the control group. The expression of p38 MAPK, TNF-α, COX-2, and MMP-9 was also attenuated by fangchinoline treatment in the kidney tissues of DN rats. Together, the results of this study suggest that fangchinoline protects against nephron damage by attenuating alterations in the p38 MAPK pathway, thereby reducing oxidative stress and inflammation in DN rats.
Keywords: fangchinoline; diabetic nephropathy; MAPK; inflammatory mediators; STZ